Effectiveness and experiences of the Extension for Community Healthcare Outcomes (ECHO) Model in developing competencies among healthcare professionals: a mixed methods systematic review protocol - Chicoine, Gabrielle; Côté, José; Pepin, Jacinthe; Fontaine, Guillaume; Maheu-Cadotte, Marc-André; Hong, Quan N.; Rouleau, Geneviève; Ziegler, Daniela; Jutras-Aswad, Didier (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background The Extension for Community Healthcare Outcomes (ECHO) Model of continuing tele-education is an innovative guided-practice model aiming at amplifying healthcare professionals’ competencies in the management of chronic and complex health conditions. While data on the impact of the ECHO model is increasingly available in the literature, what influences the model effectiveness remains unclear. Therefore, the overarching aim of this systematic review is to identify, appraise, and synthesize the available quantitative (QUAN) and qualitative (QUAL) evidence regarding the ECHO Model effectiveness and the experiences/views of ECHO’s participants about what influences the development of competencies in healthcare professionals. Methods The proposed systematic review was inspired by the Joanna Briggs Institute (JBI) methodology for Mixed Methods Systematic Reviews (MMSR) and will follow a convergent segregated approach. A systematic search will be undertaken using QUAN, QUAL and mixed methods (MM) studies of ECHO-affiliated programs identified in six databases. A publication date filter will be applied to find the articles published from 2003 onwards. Sources of unpublished studies and gray literature will be searched as well. Retrieved citations will independently be screened by two reviewers. Disagreements will be resolved through discussion until a consensus is reached or by including a third reviewer. Studies meeting the predefined inclusion criteria will be assessed on methodological quality and the data will be extracted using standardized data extraction forms. Separate QUAN and QUAL synthesis will be performed, and findings will be integrated using a matrix approach for the purpose of comparison and complementarity. Discussion This MMSR will fulfill important gaps in the current literature on the ECHO Model as the first to provide estimates on its effectiveness and consider simultaneously the experiences/views of ECHO’s participants. As each replication of the ECHO Model greatly varies depending on the context, topic, and targeted professionals, a better understanding of what influences the model effectiveness in developing healthcare professionals’ competencies is crucial to inform future implementation. Systematic review registration PROSPERO CRD42020197579